Topological analysis of migration flows (the case of political refugees). (2017) - Guarascio, Francesco; Farina, Lorenzo
In this paper, using complex network theory we analyse the problem of illegal immigration on a worldwide scale. This approach appears to be appropriate in view of the invariance of scale property that we found in real data. The presented networks have been obtained using publicly available data collected from 2000 to 2011 by the UNHCR database (asylum-seekers) which is reasonably reliable, complete and regularly updated. Preliminarily, we show the roles played by a number of key nodes and clusters. Then, to find 'important' nodes, we use a role definition which is a variant of that introduced by Guimerà and Amaral (the so-called cartography approach). Finally, a coloured cartography of the clusters obtained through a geopolitical map of the world provides an easy-to-read visual tool to highlight results in a way also suitable to a broader non-technical audience.